2023
DOI: 10.3390/ijms241210337
|View full text |Cite
|
Sign up to set email alerts
|

The Recent Research Progress of NF-κB Signaling on the Proliferation, Migration, Invasion, Immune Escape and Drug Resistance of Glioblastoma

Abstract: Glioblastoma multiforme (GBM) is the most common and invasive primary central nervous system tumor in humans, accounting for approximately 45–50% of all primary brain tumors. How to conduct early diagnosis, targeted intervention, and prognostic evaluation of GBM, in order to improve the survival rate of glioblastoma patients, has always been an urgent clinical problem to be solved. Therefore, a deeper understanding of the molecular mechanisms underlying the occurrence and development of GBM is also needed. Lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 153 publications
0
2
0
Order By: Relevance
“…Under conditions of an immunosuppressive microenvironment, the expression of immune checkpoint receptors (including CTLA4 and PD‐1) is dramatically increased. These receptors are expressed on the surface of T cells and play a negative regulatory role in T cell activation, avoiding immune overactivation and inducing immune escape and drug resistance 61,62 . Selective splicing is the process of generating different mRNA splice isoforms from mRNA precursors by different splicing methods and can result in tumor drug resistance 63,64 .…”
Section: Advances In Chemotherapy For Gliomamentioning
confidence: 99%
See 1 more Smart Citation
“…Under conditions of an immunosuppressive microenvironment, the expression of immune checkpoint receptors (including CTLA4 and PD‐1) is dramatically increased. These receptors are expressed on the surface of T cells and play a negative regulatory role in T cell activation, avoiding immune overactivation and inducing immune escape and drug resistance 61,62 . Selective splicing is the process of generating different mRNA splice isoforms from mRNA precursors by different splicing methods and can result in tumor drug resistance 63,64 .…”
Section: Advances In Chemotherapy For Gliomamentioning
confidence: 99%
“…These receptors are expressed on the surface of T cells and play a negative regulatory role in T cell activation, avoiding immune overactivation and inducing immune escape and drug resistance. 61 , 62 Selective splicing is the process of generating different mRNA splice isoforms from mRNA precursors by different splicing methods and can result in tumor drug resistance. 63 , 64 This may be related to the level of RNA‐binding proteins, mutations in splice sites, or regulatory elements.…”
Section: Advances In Chemotherapy For Gliomamentioning
confidence: 99%
“…Apart from its immunological role, chronic activation of NF-κB has now been established as a promoter of tumor initiation and progression by modulating key cellular processes such as angiogenesis, metabolism reprogramming, and tumor metastasis (Xia et al, 2014). Intriguingly, NF-κB-mediated inflammation may promote the proliferation of GBM tumor; this has further been reviewed by Shi et al (2023). Avci et al (2020) reported that administering NF-κB inhibitors alleviates the progression of tumor formation and the proliferation of patient-derived GBM cells.…”
Section: Introductionmentioning
confidence: 99%